2020
DOI: 10.1590/01047760202026022725
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical and Flame Retardant Properties of Medium Density Fiberboard Using Artificial Neural Network

Abstract: The ANN prediction model is a quite effective tool for modeling properties of MDF. At a low press temperature, the negative effect of the fire retarding agents was maximum. A reverse relation was observed between the changes in the mass loss of the fiberboard during the firing test and the MOR. Improvement in properties of MDF can be achieved by the less experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…MAPE values of artificial networks estimating the surface roughness of different materials under different machining conditions were reported as 3,866 for solid wood material (Pinus sylvestris) Gurgen et al (2022) and 20,18 for massive wooden edge-glued panels (Sofuoglu, 2015). If the (MAPE) values are less than 10%, it is considered acceptable for a prediction with high accuracy (Nazerian et al, 2020). In this study, MAPE value was calculated as 6.61, which can be considered a good prediction.…”
Section: Resultsmentioning
confidence: 99%
“…MAPE values of artificial networks estimating the surface roughness of different materials under different machining conditions were reported as 3,866 for solid wood material (Pinus sylvestris) Gurgen et al (2022) and 20,18 for massive wooden edge-glued panels (Sofuoglu, 2015). If the (MAPE) values are less than 10%, it is considered acceptable for a prediction with high accuracy (Nazerian et al, 2020). In this study, MAPE value was calculated as 6.61, which can be considered a good prediction.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Nazerian et al [ 98 ], an ANN demonstrated its prediction capability in the estimation of the modulus of rupture (MOR) and mass loss (MLoss) of flame-retardant fiberboard. The researchers applied the response surface methodology and central composite rotatable design to prepare the experimental design.…”
Section: Application Of Ai/ml For Flame-retardant Materialsmentioning
confidence: 99%
“…The structure of the ANN model to compute the fiberboard properties under fire conditions. Adapted with permission from ref [98]…”
mentioning
confidence: 99%
See 1 more Smart Citation